2021
DOI: 10.3889/oamjms.2021.5941
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Curcuma longa Extract in Combination with Phyllanthus niruri Extract in Regulating Annexin A2, Epidermal Growth Factor Receptor, Matrix Metalloproteinases, and Pyruvate Kinase M1/2 Signaling Pathway on Breast Cancer Stem Cell

Abstract: AIM: This study aimed to investigate the synergistic effects of the combination between Curcuma longa extract (CL) and Phyllanthus niruri extract (PN) in inhibiting optimally the MDA-MB-231 breast cancer stem cells (BCSCs) growth and metastatic by exploring the target and molecular mechanism using integrative bioinformatics approaches and in vitro. METHODS: CL and PN extracts were prepared by maceration method using ethanol 70%. The antiproliferative effect of CL and PN single and combination treatment was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 60 publications
2
9
0
Order By: Relevance
“…This finding supported the previous study revealed that MSCs-mediated immunosuppression mainly acts through the secretion of soluble molecules that are induces or upregulated indoleamine 2,3-dioxygenase [23], [26]. In addition, MSCs released soluble factor of anti-inflammation such as IL-10 and growth factor including transforming growth factor-ß, fibroblast growth factor, platelet-derived growth factor, and VEGF [27], [28]. This obvious reduction even exceeds the combination of MSCs and bovine colostrum due to insignificant role of bovine colostrum in the early inflammatory phase of liver fibrosis.…”
Section: Discussionsupporting
confidence: 90%
“…This finding supported the previous study revealed that MSCs-mediated immunosuppression mainly acts through the secretion of soluble molecules that are induces or upregulated indoleamine 2,3-dioxygenase [23], [26]. In addition, MSCs released soluble factor of anti-inflammation such as IL-10 and growth factor including transforming growth factor-ß, fibroblast growth factor, platelet-derived growth factor, and VEGF [27], [28]. This obvious reduction even exceeds the combination of MSCs and bovine colostrum due to insignificant role of bovine colostrum in the early inflammatory phase of liver fibrosis.…”
Section: Discussionsupporting
confidence: 90%
“… 43 Recently in 2021, a study showed the effective combination of P. niruri extract with Curcuma longa extract for treating metastatic breast cancer stem cells. 18 Herein, this is the first study investigating the potential anticancer activity of compounds derived from Phyllanthus species against resistant breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Phyllanthus niruri L. (Syn Phyllanthus amarus Schum & Thonn, family Phyllanthaceae) is a small herb widely distributed in tropical areas worldwide (such as India, China, Java, Southern Florida, and Bahamas), extensively used in ethnopharmacology for the treatment of diabetes, hypertension, and jaundice . Recently, researchers have shown a growing interest in evaluating the anticancer activity of this herb . The whole plant has diverse biological activities such as anti-inflammatory, antitumor, antinociceptive, and antioxidant properties .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify the different pathways of cell death-either necrosis or apoptosis in treated cancer cells with extracts, staining with annexin V and propidium iodide (PI) were used for determination of the early stages of apoptosis and both necrosis and late apoptosis, respectively 11 - 13 . In MCF-7/HER2+ breast cancer cells, extracts increased significantly the apoptotic cells in dose-dependent manner than untreated cells.…”
Section: Apoptosis Analysis Of Alpinia Galanga Extract On Mcf-7/her2+mentioning
confidence: 99%